2000
DOI: 10.4319/lo.2000.45.2.0459
|View full text |Cite
|
Sign up to set email alerts
|

Declining carrying capacity in the Bering Sea: Isotopic evidence from whale baleen

Abstract: The Bering Sea is a rich marine ecosystem with 1995 U.S. landings of finfish and shellfish in excess of 2 × 106 tons. Recently, major declines of marine mammal and bird populations have occurred, with the question arising as to whether the causes were top down, i.e., from fishing pressure, or bottom‐up, i.e., driven by climate‐change effects. We assessed the latter scenario by using the inverse relationship between phytoplankton cell‐growth rates and carbon isotope fractionation to compare seasonal rates of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
127
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(137 citation statements)
references
References 14 publications
5
127
0
1
Order By: Relevance
“…* Seasonal and inter-annual variability of d 15 N at the middle shelf site M2 were pronounced. Interannual and seasonal changes in nutrient supply are probably responsible for much of the variability in d 15 N. * Our data are consistent with a relationship between d 13 C and primary productivity, and hence lend some support to the Schell (2000) inference that decreasing d 13 C of bowhead whale baleen indicates declining Bering Sea productivity over the past 30 years. However, we can not rule out other factors influencing d 13 C, such as phytoplankton species effects.…”
Section: Discussionsupporting
confidence: 75%
“…* Seasonal and inter-annual variability of d 15 N at the middle shelf site M2 were pronounced. Interannual and seasonal changes in nutrient supply are probably responsible for much of the variability in d 15 N. * Our data are consistent with a relationship between d 13 C and primary productivity, and hence lend some support to the Schell (2000) inference that decreasing d 13 C of bowhead whale baleen indicates declining Bering Sea productivity over the past 30 years. However, we can not rule out other factors influencing d 13 C, such as phytoplankton species effects.…”
Section: Discussionsupporting
confidence: 75%
“…5). The δ 13 C values in bowhead whale baleen and steller sea lions bone collagen (Schell, 2000(Schell, , 2001Hirons et al, 2001) also declined at an enhanced rate; therefore, an algal-specific effect or site-specific variability were unlikely to be the primary cause of the decline observed in our study. It would appear more likely that changes in the δ 13 C DIC pool to which Keeling et al (2001); http://scrippsco2.ucsd.edu/ data/flask co2 and isotopic/monthly iso/monthly ptb c13.csv), (B) the δ 13 C values from the baleen of bowhead whales (data from Schell et al (2001)), (C) the δ 13 C values from algal specimen AM-KR-80 and combined δ 13 C values from specimens Attu 11-4 (1937-1967) and AM4-1 andAttu 11-4 (1968-2003) with line of best fit calculated using SigmaPlot (Systat Software Inc., San Jose, CA), and (D) ALPI values (data from Beamish et al (1997); http://www.pac.dfo-mpo.gc.ca/science/species-especes/ climatology-ie/cori-irco/indices/alpi.txt).…”
Section: Long-term Decrease In δ 13 C Valuesmentioning
confidence: 72%
“…Decreases in primary productivity would increase the amount of CO 2 in surface waters, thus reducing carbon fractionation during the calcification process and leading to lower δ 13 C values in the resulting skeleton. In fact, a decline in phytoplankton cell growth rates, and hence primary productivity, has been hypothesized to drive the declining trends in the whale baleen and sea lion bone collagen δ 13 C (Schell, 2000(Schell, , 2001Hirons et al, 2001). However, available evidence does not support a decrease in new primary production (Hunt Jr et al, 2002).…”
Section: Long-term Decrease In δ 13 C Valuesmentioning
confidence: 99%
“…Also, we were interested in comparing feeding strategies in recent vs. earlier years. Recent evidence that the productivity of the Bering and Chukchi Seas may have declined suggested that feeding in the eastern Beaufort Sea might be more important to bowhead whales now than in previous decades (Schell 2000(Schell , 2001. As in earlier related studies, our approach was based on the fact that samples of bowhead tissues can be obtained in northern Alaska during the spring and autumn migrations, when bowhead whales are harvested by Inupiat hunters (Stoker & Krupnik 1993).…”
Section: Introductionmentioning
confidence: 99%